Harbour seal movements and haul-out patterns:implications for monitoring and management - Cunningham, Louise; Baxter, John M.; Boyd, Ian Lamont; Duck, Callan D.; Lonergan, Mike; Moss, Simon E.; McConnell, Bernie (Aquatic Conservation: Marine and Freshwater Ecosystems, 2009)
1. Compliance with conservation legislation requires knowledge on the behaviour, abundance and distribution of protected species. Seal life history is characterized by a combination of marine foraging and a requirement to haul out on a solid substrate for reproduction and moulting. Thus understanding the use of haul out sites, where seals are Counted, its well as their at-sea movements is crucial for designing effective monitoring and management plans. 2. This study used satellite transmitters deployed on 24 harbour seals in western Scotland to examine movements and haul-out patterns. 3. The proportion of time harbour seals spent hauled Out (daily means of between 11 and 27%) varied spatially, temporally and according to sex. The mean haul-out duration was 5 h, with a maximum of over 24 h. 4. Patterns of movement were observed at two geographical scales; while some seals travelled over 100 km, 50% of trips were within 25 km of a haul-out site. These patterns are important for the identification of a marine component to designated protected areas for the species. 5. On average seals returned to the haul-out. sites they last used during 40% of trips, indicating a degree of site fidelity, though there was wide variation between different haul-out sites (range 0% to > 75%). 6. Low fidelity haul-out sites could form a network of land-based protected areas, while high fidelity sites might form appropriate management units. Copyright (c) 2008 John Wiley & Sons, Ltd.